Vibro-isolation suspension with quasi-zero stiffness for vibroactive equipment - Yu. A. Burian; M. V. Silkov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The work is devoted to the theory of vibration isolation of vibroactive objects, for example: engines, generators, pumps, compressors, fans, pipelines etc. A new design of vibration isolation suspension with quasi-zero stiffness is proposed, its mathematical model is obtained, which allows choosing its main parameters. Computer calculations have been performed that show that a significant shift in the natural frequency of the suspension towards low frequencies in comparison with relying only on coil springs with the same static load allows reducing the coefficient of transmission of force to the base at operating frequencies. The latter makes it possible to improve the vibration isolation of various technological objects